Diversity Genetic of Butterfly Ornithoptera spp in Bacan Island Based on Morphological and environmental Factor Analysis - Mas'ud, Abdu; Sundari, Sundari; Alisi, Alisi (SAINTIFIK@: Jurnal Pendidikan MIPA, 2025)
Ornithoptera sp in Bacan Island is an endemic butterfly. Ornithoptera croesus in Bacan Island empirically has a variety of morphological characters. The purpose of this study was to determine the dissimilarity of specific characteristics of O. croesus based on morphometric analysis on environmental factors, especially elevation gradients. Data from morphometric character measurements were analyzed using UPGMA cluster analysis. The results showed that the intraspecific dissimilarity of O. croesus on elevation gradients in the Sibela Mountains Nature Reserve area, Bacan Island, was in the low category. Elevation gradients were not the main factor in determining intraspecific dissimilarity. Migration factors and the availability of food plants that determine the pattern of O. croesus, can be seen from the highest similarity value in the dendogram found in O. croesus ♀ 800 masl with O. croesus ♀ 20 masl. Migration factors and the availability of food crops cause the grouping pattern to be inconsistent with the results of the biplot analysis of environmental factor data which groups lowlands and midlands in one cluster